KEPASTIAN HUKUM DAN PERLINDUNGAN HUKUM KEPEMILIKAN HAK ATAS TANAH - Eman Sulaiman (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2022)
This article describes legal certainty and legal protection of land rights ownership with a formal juridical approach. From the results of the study, it is understood that the concept of ownership of land rights is a hereditary right, the strongest and fulfilled compared to other land rights. Ownership rights to land can only be owned by a single Indonesian citizen, and certain legal entities are regulated in Government Regulation Number 38 of 1963. Legal certainty regarding land rights to provide certainty regarding the object of land rights, certainty regarding the subject of land rights and certainty regarding the status of land rights. Legal conception, land rights certificates are evidence issued by authorized legal institutions (BPN), which contain juridical data and physical data used as evidence of land rights ownership with the aim of providing legal certainty and certainty of rights to a plot of land. owned or owned by a person or legal entity. With the certificate of rights, it is expected that juridically it can provide legal certainty and rights by the state for holders of land rights. This state guarantee is given to the owner or certificate holder because the land is already registered in the state land administration system.